Characterization of slow cycling corneal limbal epithelial cells identifies putative stem cell markers - R. Sartaj (Nature Portfolio, 2017)
Abstract In order to identify reliable markers of corneal epithelial stem cells, we employed an inducible transgenic “pulse-chase” murine model (K5Tta × TRE-H2BGFP) to localize, purify, and characterize slow cycling cells in the cornea. The retention of GFP labeling in slowly dividing cells allowed for localization of these cells to the corneal limbus and their subsequent purification by FACS. Transcriptome analysis from slow cycling cells identified differentially expressed genes when comparing to GFP- faster-dividing cells. RNA-Seq data from corneal epithelium were compared to epidermal hair follicle stem cell RNA-Seq to identify genes representing common putative stem cell markers or determinants, which included Sox9, Fzd7, Actn1, Anxa3 and Krt17. Overlapping retention of GFP and immunohistochemical expression of Krt15, ΔNp63, Sox9, Actn1, Fzd7 and Krt17 were observed in our transgenic model. Our analysis presents an array of novel genes as putative corneal stem cell markers.